Ubiquitination and Alzheimer related disorders - Mayer, John (Henry Stewart Talks, 2007)
Alzheimer's disease and dementia with Lewy bodies, Ubiquitin and the ubiquitin pathway of intracellular proteolysis, Ubiquitin immunocytochemistry in understanding chronic neurodegenerative disease, Ubiquitin and the discovery of dementia with Lewy bodies, Importance of ubiquitin for normal brain functions, Ubiquitin and Parkinson's disease, Intraneuronal protein aggregation and neurodegenerative disease, Experimental demonstration of generic gene expression changes in response to protein aggregates, Expression of the mitogen activated protein kinase (MEK5), ERK5 kinase module in Alzheimer's disease and dementia with Lewy bodies, Ubiquitin-p62-MEK5/ERK5 pathway of neuronal survival in Alzheimer related disorders, Diagnostic and therapeutic importance of ubiquitin/kinase mediated neuronal survival and anti-apoptotic pathways